Alterations in Brain Network Topology and Structural-Functional Connectome Coupling Relate to Cognitive Impairment - Wang, Juan; Khosrowabadi, Reza; Ng, Kwun Kei; Hong, Zhaoping; Chong, Joanna Su Xian; Wang, Yijun; Chen, Chun-Yin; Hilal, Saima; Venketasubramanian, Narayanaswamy; Wong, Tien Yin; Chen, Christopher Li-Hsian; Ikram, Mohammad Kamran; et al. (Frontiers in Aging Neuroscience, 2018)
According to the network-based neurodegeneration hypothesis, neurodegenerative diseases target specific large-scale neural networks, such as the default mode network, and may propagate along the structural and functional connections within and between these brain networks. Cognitive impairment no dementia (CIND) represents an early prodromal stage but few studies have examined brain topological changes within and between brain structural and functional networks. To this end, we studied the structural networks [diffusion magnetic resonance imaging (MRI)] and functional networks (task-free functional MRI) in CIND (61 mild, 56 moderate) and healthy older adults (97 controls). Structurally, compared with controls, moderate CIND had lower global efficiency, and lower nodal centrality and nodal efficiency in the thalamus, somatomotor network, and higher-order cognitive networks. Mild CIND only had higher nodal degree centrality in dorsal parietal regions. Functional differences were more subtle, with both CIND groups showing lower nodal centrality and efficiency in temporal and somatomotor regions. Importantly, CIND generally had higher structural-functional connectome correlation than controls. The higher structural-functional topological similarity was undesirable as higher correlation was associated with poorer verbal memory, executive function, and visuoconstruction. Our findings highlighted the distinct and progressive changes in brain structural-functional networks at the prodromal stage of neurodegenerative diseases.